2017
DOI: 10.7150/ijms.19929
|View full text |Cite
|
Sign up to set email alerts
|

Urinary UBC Rapid and NMP22 Test for Bladder Cancer Surveillance in Comparison to Urinary Cytology: Results from a Prospective Single-Center Study

Abstract: Background: Non-muscle invasive bladder cancer (NMIBC) is associated with high rates of recurrence, resulting in frequent follow-up cystoscopies. We evaluated the use of two point-of-care tests - the nuclear matrix protein 22 (NMP22) and urinary bladder cancer antigen (UBC) Rapid - compared to routine follow-up in patients with a previous history of NMIBC. Methods: 31 patients with cystoscopy-verified active bladder cancer, and 44 follow-up patients without disease as confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 35 publications
7
43
0
1
Order By: Relevance
“…In contrast to its rather low sensitivity, cytology exhibited excellent specificity (96.87%), without statistically significant differences compared to the other tests (BTA: 89.79%; UBC: 86.73% and TPS: 54.08%). In line with our results, several reports [11,13,14,19,20] showed that compared to urine cytology, UBC alone revealed higher sensitivity in detecting low-grade bladder tumors and lower specificity. As for TPS, we have not found studies that analyze its diagnostic performance for prediction of NMIBC.…”
Section: Resultssupporting
confidence: 92%
“…In contrast to its rather low sensitivity, cytology exhibited excellent specificity (96.87%), without statistically significant differences compared to the other tests (BTA: 89.79%; UBC: 86.73% and TPS: 54.08%). In line with our results, several reports [11,13,14,19,20] showed that compared to urine cytology, UBC alone revealed higher sensitivity in detecting low-grade bladder tumors and lower specificity. As for TPS, we have not found studies that analyze its diagnostic performance for prediction of NMIBC.…”
Section: Resultssupporting
confidence: 92%
“…However, there is no new consensus indicator on the risk factors for the recurrence of NMIBC, especially the lack of relevant tumor indicators in urine. Urine BLCA-4, BTA, NMP22, and CEA can be used as important markers for the diagnosis and recurrence monitoring of bladder cancer [23][24][25][26][27][28][29][30]. At present, the specificity and sensitivity of BLCA-4 detection for bladder cancer diagnosis have reached a high level.…”
Section: Discussionmentioning
confidence: 99%
“…NMP22 is mainly involved in DNA replication and transcription, RNA synthesis and gene expression regulation, and its content can be determined by detecting the amount of protein released by apoptotic cells [28]. Related studies have shown that NMP22 content is positively correlated with tumor size, stage, and grade [29]. CEA is a tumor-associated antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Недавно были опубликованы 4 исследования сравнения маркеров, в которых сообщается о низкой чувствительности (11-58 %) качественного теста в диагностике рецидива РМП [9,[10][11][12]. В связи с этим высказывается предположение о том, что этот тест может быть полезен при принятии решения о немедленной либо отсроченной цистоскопии в зависимости от индивидуальной схемы наблюдения [13].…”
Section: Nmp22unclassified